Analisis Tingkat Kemiskinan dan Indeks Pembangunan Manusia (IPM) Kabupaten/ Kota di Provinsi Sumatera Barat - Maryuni, Elza; Mahmud; Gusvita, Herda (Jurnal Research Ilmu Pertanian, 2022)
Poverty and the Human Development Index are important indicators to achieve the success of a country's development. Poverty is a complex problem that is still difficult to solve in almost every region. This then triggers the emergence of inequality in society. The purpose of this study is to analyze the effect of Gross Regional Domestic Product (GRDP), population growth, investment and the Human Development Index (IPM) on poverty levels and analyze the effect of Gross Regional Domestic Product (GRDP), unemployment rates and poverty rates on the Human Development Index (IPM)). This research was conducted from June 16 to July 16, 2021 in districts/cities of West Sumatra Province using secondary data for 2019-2020. The data analysis method used is Two Stage Least Squadrat (2SLS) with a simultaneous equation model facilitated by the eviews 9 application software. The results show that GRDP, population growth and investment have no significant effect on the poverty level, while HDI has a significant effect on the poverty level (0,05 ≥ 0,001). Then GRDP, unemployment rate and poverty rate have no significant effect pn HDI.